Comparative analysis of feeding techniques for cylindrical surrounding patch antenna - Erhiega N. Umayah; Viranjay M. Srivastava (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this research work, a Cylindrical Surrounding Patch Antenna (CSPA) with improved performance parameters based on inset feed method compared to other feed techniques has been proposed for 1.8 GHz applications. The designed and simulated CSPA is a rotary version of an initially designed Rectangular Planar Patch Antenna (RPPA). The RPPA is mounted on a cylindrical surface with radius (r) 10 mm which is an increased curvature for better -10 dB S-parameter (S11), impedance Band Width (BW), Voltage Standing Wave Ratio (VSWR), radiation pattern, and gain. The copper radiating patch has been conformed on the surface of the grounded flexible polyimide substrate with relative permittivity (εr) 3.5 and thickness (h) 1.6 mm at normalized input impedance of 50 Ω. Results for the RPPA and the proposed CSPA have been compared with existing designs in terms of antenna size, resonant frequency (fr), return loss (S11), and gain while taking cognizance of the feeding techniques. The S11, BW, VSWR, and gain are -12.784 dB, 28 MHz, 1.8, and 4.81 dBi respectively for the rectangular planar patch antenna and -35.571 dB, 66 MHz, 1.5, and 3.74 dBi, respectively for the cylindrical surrounding patch antenna.